Isolation and characterization of micrornas from two different fruit ripening stages in pineapples - Yew, Che Wei (2011)
Plant microRNAs are single-stranded small RNAs with approximately 21-24 nucleotides in size. They play an important role in regulating gene expression at the post-transcriptional level through complementary binding to endogenous mRNA targets which subsequently induces gene silencing. Although pineapple is an important tropical non-climacteric fruit, the regulatory roles of miRNAs in fruit ripening remains unknown. Thus, this study aims to isolate miRNAs from an unripe pineapple fruit, to predict the targeted genes, and to profile the expression levels of selected miRNAs between unripe and ripe fruits. MicroRNAs were isolated through the construction of a small RNA library. The target genes of the isolated miRNAs were then identified with online bioinformatics tools. Subsequently, the expression profiles between unripe and ripe fruits of randomly selected miRNAs were determined through quantitative stem-loop real-time PCR. The construction of sRNA library yielded 1,706 redundant sRNAs. This includes 13 miR/miR* families, namely miR156, miR157, miR159, miR162, miR164, miR166, miR167*, miR171, miR319, miR395, miR396, miR529 and miR827. Among these, miR157/miR157* were the most abundant miRNAs, constituting of 10.9% of the isolated sRNAs. Expression analysis showed that miR157 is 1.6x fold depressed in the ripe fruit, as compared to the unripe fruit. Meanwhile, miR395 showed the most significant induced expression (20x fold) while miR529 is depressed 33.3x fold, in the ripe fruit. miR157 was predicted to target SPL gene which is involved in phase transition from the unripe to ripe stage of the fruit. miR395 was predicted to target ATPsulfurylase which may facilitate the accumulation of glucosinolates as a defence mechanism against the opportunistic infection by microbes and fungus during fruit ripening. Whereas, miR529 was postulated to target AP2/ERF, a ethylene-response transcription factor that regulates the expression of ethylene-responsive chitinase and defensins, as a defense against pathogenic infections. Overall, miR157, miR395 and miR529 were postulated to be key regulators during the fruit ripening of pineapples, which respectively involved in phase transition and defence against pathogenic infections. The information provided here will be useful in understanding the roles of miRNAs in the process of ripening, particularly in nonclimacteric fruits.